How to Be an Ethical Expressivist. (13th September 2014) - Silk, Alex
<x xml:space="preserve">Abstract</x> Expressivism promises an illuminating account of the nature of normative judgment. But worries about the details of expressivist semantics have led many to doubt whether expressivism's putative advantages can be secured. Drawing on insights from linguistic semantics and decision theory, I develop a novel framework for implementing an expressivist semantics that I call ordering expressivism. I argue that by systematically interpreting the orderings that figure in analyses of normative terms in terms of the basic practical attitude of conditional weak preference, the expressivist can explain the semantic properties of normative sentences in terms of the logical properties of that attitude. Expressivism's problems with capturing the logical relations among normative sentences can be reduced to the familiar, more tractable problem of explaining certain coherence constraints on preferences. Particular attention is given to the interpretation of wide‐scope negation. The proposed solution is also extended to other types of embedded contexts—most notably, disjunctions.